2014
DOI: 10.1523/jneurosci.0510-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Influence of Rhythmic Cortical versus Cerebellar Transcranial Stimulation on Human Physiological Tremor

Abstract: The influence of central neuronal oscillators on human physiological tremor is controversial. To address this, transcranial alternating current stimulation (TACS) was delivered at peak tremor frequency to 12 healthy volunteers in a 2 ϫ 2 crossover study. Two sites were stimulated [contralateral primary motor cortex (M1), vs ipsilateral cerebellum] while participants performed two types of tasks designed to probe the different manifestations of physiological tremor of the hand-kinetic and postural tremor. Tremo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 59 publications
0
36
0
1
Order By: Relevance
“…Current density modelling suggests that this montage with the reference on the shoulder provides maximal current flow within the cerebellar hemispheres (Parazzini et al 2014;Rahman et al 2014). Moreover, electrode montages with reference on the shoulder have been used successfully in a few stimulation studies (Joundi et al 2012;Brittain et al 2013;Mehta et al 2014Mehta et al , 2015. Finally, in a recent study using a similar montage, we found that TDCS over the cerebellum affected saccadic adaptation in a polarity-dependent manner (Panouillères et al 2015).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Current density modelling suggests that this montage with the reference on the shoulder provides maximal current flow within the cerebellar hemispheres (Parazzini et al 2014;Rahman et al 2014). Moreover, electrode montages with reference on the shoulder have been used successfully in a few stimulation studies (Joundi et al 2012;Brittain et al 2013;Mehta et al 2014Mehta et al , 2015. Finally, in a recent study using a similar montage, we found that TDCS over the cerebellum affected saccadic adaptation in a polarity-dependent manner (Panouillères et al 2015).…”
Section: Discussionmentioning
confidence: 64%
“…; Mehta et al . , ). Finally, in a recent study using a similar montage, we found that TDCS over the cerebellum affected saccadic adaptation in a polarity‐dependent manner (Panouillères et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example using motor cortex TACS to reduce tremor in Parkinson’s disease, actigraphy from the tremulous limb was adopted as a proxy for central neural activity (Brittain et al, 2013). The approach involved an initial open-loop followed by a closed-loop intervention that afforded several key advantages: First, knowledge of phase information for both TACS waveform and target oscillations (made possible by the proxy measure of central activity) permitted a direct measure of entrainment (Mehta et al, 2014, 2015, Brittain et al, 2015). Second, the phase-precession associated with open-loop stimulation permitted the construction of a stimulus response profile, in order to identify the most effective stimulation parameters for tremor suppression.…”
Section: Future Perspective: Optimization Of the Approachmentioning
confidence: 99%
“…In addition, in several studies entrainment has been reported to be weak (Mehta et al, 2014, 2015, Brittain et al, 2015). Since open-loop protocols rely on assumptions about underlying mechanisms (e.g.…”
Section: Future Perspective: Optimization Of the Approachmentioning
confidence: 99%